Laparoscopic Spleen-Preserving Decapsulation of the Splenic Cyst: A Case Report - Vijay N; Muvva Sri Harsha M; Prasanna Kumar Reddy (National Board of Examinations Journal of Medical Sciences, 2024)
Worldwide the Incidence of Primary nonparasitic splenic cysts are rare. They were incidentally diagnosed while evaluating other diseases by imaging. We here by present our experience of a case of 23-year-old woman, with a primary nonparasitic splenic cyst. The patient underwent laparoscopic spleen-preserving decapsulation of the splenic cyst. The patient recovered well and had no postoperative complications.